Inhibition of Jak/STAT signaling reduces the activation of pancreatic stellate cells in vitro and limits caerulein-induced chronic pancreatitis in vivo - Hannah M. Komar (Nature Portfolio, 2017)
Abstract Chronic pancreatitis (CP) is a fibro-inflammatory disease leading to pain, maldigestion, and pancreatic insufficiency. No therapeutic options exist due to a limited understanding of the biology of CP pathology. Recent findings implicate pancreatic stellate cells (PSC) as prominent mediators of inflammatory and fibrotic processes during CP. Here, we utilized primary and immortalized PSC obtained from mice and patients with CP or pancreatic cancer to examine the effect of Jak/STAT and MAPK pathway inhibition in vitro. The well-characterized caerulein model of CP was used to assess the therapeutic efficacy of Jak1/2 inhibition in vivo. Treatment of cultured PSC with the Jak1/2 inhibitor ruxolitinib reduced STAT3 phosphorylation, cell proliferation, and expression of alpha-smooth muscle actin (α-SMA), a marker of PSC activation. Treatment with the MAPK inhibitor, MEK162, had less consistent effects on PSC proliferation and no impact on activation. In the caerulein-induced murine model of CP, administration of ruxolitinib for one week significantly reduced biomarkers of inflammation and fibrosis. These data suggest that the Jak/STAT pathway plays a prominent role in PSC proliferation and activation. In vivo treatment with the Jak1/2 inhibitor ruxolitinib reduced the severity of experimental CP, suggesting that targeting Jak/STAT signaling may represent a promising therapeutic strategy for CP.